Estudio Limnológico preliminar de la Laguna Hule, Costa Rica (ING) - Ramírez R., Elizabeth (1991)
The “Laguna Hule” a medium size volcanic lake, is located at 750m above sea level on the Caribbean side of the Cordillera Volcánica Central in Costa Rica. Hule is one of three in a lake complex known as “Bosque Alegre”. The lake area is 60.3 ha and its maximum depth reaches 22.5 m.Some selected physical and chemical features were measured and discussed here. Dissolved oxygen exhibits a clinograde profile, with 60% of the water volume being anoxic and containing hydrogen sulphide H2S  below 8m depth. The temperature profile shows a maximum difference of 4.2 °C showing stratification during the study period. The lake is of the bicarbonate type with a high concentration of Fe+2 in the hypolimnion.